(untitled) (El Taco en la Brea, 2025)
The purpose of this paper is to take a brief look at some of the notions with which critics thought about the work of the poet and visual artist Fernanda Laguna and Belleza y Felicidad, project founded by her together with Cecilia Pavón. These notions will be analyzed in dialogue with a series of poems in order to notice the transformations that her figure was assuming over the years and the movement that can be traced from the modulation of the voice of her first plaquette Poesías (1995) —with Xuxa as background music— to the verses where the self triumphantly celebrates the end of that generation with which she was read in the poem «Terminaron los 90» (2018).